Handbook of theological education in Africa - Phiri, Isabel Apawo; Werner, Dietrich; Djomhoué, Priscille; Amanze, James; Owino, Kennedy; Phiri, Stephen; Mbiti, John S.; Karamaga, André; Botman, H. Russel; Tveit, Olav Fykse; Oduyoye, Mercy Amba; Ackermann, Denise (Regnum studies in global Christianity., 2013)
This Handbook of Theological Education in Africa is a fascinating witness to the explosive nature of theological education. The historical and regional surveys, among others, open our eyes and ears to see and hear how fast it has taken root historically, geographically, and ecumenically. The landscape of African theological education changed drastically during the final twenty to thirty years of the last century. There is much to appreciate about it and about what has been achieved. We have grounds to rejoice and for which to thank the Lord.